ANALISIS PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN KOMPETENSI GURU (STUDI KASUS DI SMA NEGERI 2 MAKASSAR) - Muh. Ardiansyah; Arismunandar Arismunandar; Heriansyah Heriansyah (Bajang Institute, 2023)
The study aims at describing the roles of the principal as the supervisor to improve the teacher competence and discovering the supporting and inhibiting factors that influence it. The type of this study is a qualitative research with a case study approach which is descriptive in nature. The research data were obtained from the principal, the vice-principal for curriculum affairs, supervision team, and teachers through observation study, interview, and documentation. The research data obtained were analyzed by employing data reduction, data presentation, and conclusion drawing. Based on the research data, the roles of the principal as the supervisor at SMAN 2 Makassar in improving the teacher competence through (a) academic supervision planning are (1) forming the academic supervision, (2) compiling observation instrument, (3) scheduling academic supervision, and (4) socializing academic supervision; (b) academic supervision implementation: (1) visiting classes, (2) classroom observation, and (3) individual session; (c) follow-up academic supervision by providing guidance, assistance, and coaching through education and training program which cover: (1) In House Training (IHT), (2) workshop, and (3) subject teacher consultation (MGMP). The supporting factors in improving teacher comptence are (1) teacher’s motivation, (2) the school’s infrastructure and facility, (3) adaptive and conducive school environment, and (4) partnership between schools and education supervisors; whereas, the inhibiting factors in improving teacher competence are the situation and condition of Covid-19 pandemic.